Transition cow nutrition and management - John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 2003)
Dairy cows are generally provided with a 60-day dry period. The first part of the dry period is called the "far-off dry period" beginning at dry off and continuing until 21 days before projected calving date. The second part of the dry period is called the "close-up dry period" beginning at 21 days before projected calving date and ending at parturition. Diets formulated for far-off dry cows are generally high in forage and are designed to support body maintenance and fetal growth. Rumen function and microbial populations adjust to these diets by the end of the far-off period and require a period of adaptation before switching to a high-energy lactation diet. Thus, a close-up diet should not be formulated as an entity unto itself, but as a bridge between a low and high-energy diet, retaining some characteristics of both the far-off and lactation diets. The ultimate success of a transition cow nutrition and management program is a lactation characterized by high milk and yields of its component and an absence of ruminal, metabolic, mammary gland, and reproductive disorders. Therefore, close-up diets should encourage ruminal adaptation to subsequent lactation diets, prevent metabolic disorders, and minimize tissue mobilization prior to parturition. Rumen bacteria, protozoa, and fungi are sensitive to new diet ingredients and the amount of substrate available (dry matter intake). Thus, adequate time should be allocated to exposure to the close-up diet before parturition. Our studies indicate that cows should be offered a close-up diet that contains 13.5 to 14.5% crude protein and 35% nonfiber carbohydrate for approximately 28 days before parturition.; Dairy Day, 2003, Kansas State University, Manhattan, KS, 2003;
Keywords: Diary Day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-129-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 919; Dairy; Close-up diets; Transition cows